Correlation Between Intertidal Zone Fish Community and Water Parameters of Melasti Beach, Bali - Ray Ryther Amgra; Dwi Budi Wiyanto; Putu Satya Pratama Atmaja (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2026)
The ocean and coastal waters have incredible ecosystem diversity, especially in the intertidal zone where tidal fluctuations occur. Although considered extreme, this zone supports many organisms with specialized adaptations to the physical and chemical conditions. As a result, the biodiversity and abundance of organisms in the intertidal zone are higher than in other habitats. Previous research highlights the importance of ecosystems such as coral reefs, seagrass beds, and mangroves in supporting fish biodiversity in the intertidal zone, including ornamental and commercial species. Environmental factors such as temperature, pH, and salinity play significant roles in determining fish diversity, creating various microhabitats. Melasti Beach is the focus of research because it provides important habitats for various fish species and shows high biodiversity. This research is important for understanding and conserving the structure of intertidal fish communities. The research method consists of fish observation using Underwater Visual Census & capture, as well as measuring water parameters (salinity, pH, temperature, and phosphate), with data analysis covering species composition and abundance, ecological indices, and correlations between water parameters and species abundance. The research shows 28 fish families, totaling 74 species and 488 individuals during high tide, and 61 species and 236 individuals during low tide, with a moderate diversity index. Water parameters such as pH, temperature, salinity, and phosphate exhibit minor variations between high and low tides. During high tide, the results showed that water parameters were negatively correlated with species abundance. Similar to high tide conditions, during low tide, temperature and pH maintain a negative correlation, while salinity and phosphate are the opposite.